2018
DOI: 10.1111/jth.13975
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and inflammation in long‐term cancer survivors: results from the adult population

Abstract: Background The advances in cancer treatment and detection of early cancer have resulted in a steady increase in the number of of cancer survivors over the years. However, because of the long-term toxic effects of chemotherapy and radiotherapy, the incidence of cardiovascular disease (CVD) is increasing in survivors. Objectives To investigate traditional cardiovascular risk factors (CVRFs), inflammation and the coagulation profile in long-term cancer survivors (cancer diagnosis ≥ 5 years) from a large adult pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Hypercoagulable states have been found to be associated with cancer and crucial for tumor growth, angiogenesis and metastasis . Coagulation also influences cancer patient survival . These finding are novel and further investigation of the proteins as new biomarkers or therapeutic targets seems warranted, particularly given the high prevalence of hypercoagulability in PDAC patients and a suggested survival benefit with treatment …”
Section: Discussionmentioning
confidence: 99%
“…Hypercoagulable states have been found to be associated with cancer and crucial for tumor growth, angiogenesis and metastasis . Coagulation also influences cancer patient survival . These finding are novel and further investigation of the proteins as new biomarkers or therapeutic targets seems warranted, particularly given the high prevalence of hypercoagulability in PDAC patients and a suggested survival benefit with treatment …”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, malignant tumors are diseases that can lead to changes in the blood status of the whole body, rather than only local lesions. 10-12 Classical tumor stage is more targeted at the evaluation of the tumor lesion itself, and the inability to evaluate the patient's systemic status is also one of its defects.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies examining higher rates of D-dimer elevations in African Americans have identified a potential genetic variation of the F3 loci, believed to be associated with this elevation. 24 Studies evaluating metabolism of direct oral anticoagulants (DOACs) have also identified potential differences in sulfation of active apixaban due to SULT1A1*3, an allelic variant of SULTA1 (a polymorphic variant of a sulfotransferase or SULT), which may be associated with a moderate potential to affect the anticoagulation effects of apixaban. 70 Genome studies also describe genetic variants in vWF specific to African American women, although the resulting phenotype of these changes is not clear.…”
Section: Covid-19 Disease Trendsmentioning
confidence: 99%
“…[17][18][19][20] In addition to the conditions that render specific organ systems at risk, such as COPD and asthma, systemic diseases such as diabetes, obesity, autoimmune disorders, and cancer predispose patients to severe and rapid changes to their inflammatory system and, in many cases, also predispose a patient to being in a prothrombotic state. [21][22][23][24][25] Individuals with these preexisting conditions, along with cardiopulmonary disease, appear to be at the highest risk for development of severe COVID-19 as well as higher mortality rate. [13][14][15][16] Additionally, there is mounting evidence that a major pathological finding in severe COVID-19 is the development of macrothrombi and microthrombi.…”
mentioning
confidence: 99%